Differences in Sensation Level between the Widex SoundTracker and Two Real-Ear Analyzers. - Oeding, Kristi; Valente, Michael (Journal of the American Academy of Audiology, 2013)
Background: SoundTracker is an algorithm in Widex's Compass fitting software that could potentially be used to estimate a patient's aided sensation level (SL). SoundTracker's accuracy of estimating a patient's SL has never been verified in comparison to SL measured with commercially available real-ear analyzers. Purpose: Determine whether statistically significant differences are present between the estimated SL of the Widex SoundTracker software application and the measured SL of the Audioscan Verifit and Frye 6500 real-ear analyzers at 500, 1000, 2000, and 4000 Hz. Research Design: This study used a randomized repeated measures design to determine differences in SL between SoundTracker and the Verifit and 6500. Study Sample: Ten subjects (N 5 20 ears) were recruited who were experienced users of behind-theear hearing aids with conventional vented earmolds and had bilateral sensorineural hearing loss that was .30 dB HL below 1000 Hz and ≤70 dB HL to 4000 Hz. Data Collection and Analysis: Real-ear in-situ thresholds (dB sound pressure level [SPL]) and real-ear aided responses (REAR; dB SPL) were measured at 500, 1000, 2000, and 4000 Hz to determine differences in SL between SoundTracker, Verifit, and 6500. A three-factor repeated measures analysis of variance (ANOVA) was utilized to determine differences between method (real-ear analyzers and Sound- Tracker), analyzer (Verifit and 6500), and frequency (500, 1000, 2000, and 4000 Hz). Results: Mean differences in measured SL for the Verifit and 6500 were ≤2 dB when compared to the estimated SL using SoundTracker. A statistically significant difference in SL was present between the Verifit and SoundTracker at 2000 Hz (p, 0.01), but no significant differences were present at 500, 1000, and 4000 Hz. A statistically significant difference in SL was present between the 6500 and SoundTracker at 4000 Hz (p , 0.01), but no significant differences were present at 500, 1000, and 2000 Hz. Mean differences in measured SL between the real-ear analyzers (difference of SoundTracker SL minus Verifit SL compared to the difference of SoundTracker SL minus 6500 SL) were ≤2 dB with a statistically significant difference present at 2000 Hz (p , 0.01), but no statistically significant differences were present at 500, 1000, or 4000 Hz. Conclusions: Nearly 85% of the differences between the estimated SoundTracker SL and the measured SLs of the Verifit and 6500 were ≤2 dB. Despite some limitations of this study, SoundTracker could be useful as a counseling tool to illustrate to patients which sounds are audible or inaudible when unaided and aided.